Kemitraan Keluarga dalam Menangkal Radikalisme - Ervi Siti Zahroh Zidni (Jurnal Studi Al-Quran, 2018)
Radicalism movement is getting massive. It is a big challenge for parents to cooperate each other to educate their children. Cooperating with parents to educate their children will be more effective to prevent radicalism understanding. According to radicalism understanding about respect, Indonesia’s flag is trusted as something to be avoided on Islam, and that understanding is getting wide in the youth of Indonesian Moslems today. The method in this paper is Family partnership has been recognized as an innovative and highly impactful to avoid the radicalism. This paper use qualitative method with observations on social and family conditions as the smallest part of society. The results of this paper indicate that the role of the family is very important in preventing radicalism through the partnership between husband and wife. Education of children is not only the duty of the wife but is the responsibility of the father. Besides on the harmonious relationship between husband and wife through family partnerships into the main capital in preventing radicals.